Sensitivitas pp 78 tahun 2015 Tentang pengupahan - Ibnu Affan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
The establishment of UMP/UMK based on PP on wage is accomplished in a simple way without making survey on price. The minimum wage is determined on this PP is made by using the formula of minimum wage calculation in KHL in accordance with the productivity and economic growth. With this calculation, the rise of minimum wage could be estimated either by the employee / labor, or the entrepreneurs every year. Furthermore, it will give warranty to the entrepreneur in their entrepreneurship.  The presence of PP on wage, in fact, triggers many rejections from employee/labor because it is in contradictory with the Act of Employment which results disadvantages for employee/labor because the determination of UMK/UMP will be made without the Union of Labors but it will be decided directly by the governor without any recommendation from the regent/mayor. Keyword : Sensitivity Pp 78 Year 2015 On Wage